A fast click–slow release strategy towards the HPLC-free synthesis of RNA. Issue 7 (1st December 2015) - Agustin, E.; Asare Okai, P. N.; Khan, I.; Miller, M. R.; Wang, R.; Sheng, J.; Royzen, M.
Abstract : A general strategy for the purification of oligonucleotides synthesized by solid phase synthesis is described. Abstract : A general strategy for purification of oligonucleotides synthesized by solid phase synthesis is described. It is based on a recently developed concept involving a bio-orthogonal inverse electron demand Diels–Alder reaction between trans -cyclooctene and tetrazine, termed 'click-to-release'. The strategy has been applied towards the synthesis and purification of a model hairpin RNA strand, as well as a 34 nt long aptamer.